Mobile realities and dreams: are students and teachers dreaming alone or together? - Bassett, Mark; Kelly, Oriel (ASCILITE, 2013)
The use of mobile technologies and social media for teaching and learning signals the potential for ontological shifts in learning and teaching, redefining the roles of both students and lecturers. Understanding tertiary student perspectives on how they use wireless mobile devices for learning is crucial if their lecturers are to make informed evaluative decisions about how they use those same devices in their teaching. Lecturers require professional development in using mobile technologies in teaching, and institutions face challenges with infrastructure. This paper outlines a research proposal for exploring tertiary student use of wireless mobile devices for learning and the relationship of that to lecturer and institutional readiness in a blended learning environment. Cochrane’s (2012) six critical success factors for transforming pedagogy with mobile Web 2.0 and Puentedura’s (2012) SAMR model of technology adoption will be used as evaluative frameworks.
Keywords: Blended learning; Mobile learning; Tertiary education; Transformative education